'Profit Is Not a Dirty Word': Social Entrepreneurship and Community Development. Issue 2 (3rd May 2020) - Duarte Alonso, Abel; Kok, Seng; O'Brien, Seamus
Abstract: This exploratory study proposes a theoretical framework based on Max Weber's types of rationality to understand the motivations for and operationalization of social entrepreneurship (SE), drawing from the case of Homebaked, an organization operating in Liverpool, UK. Face-to-face interviews with nine Homebaked's members, including management, were complemented by several on-site observations, industry and consulting report reviews. A juxtaposition between entrepreneurship and SE emerged, in that for-profit principles were implemented to drive and achieve objectives of social causes. From a theoretical perspective, a strong connection was revealed between the findings and all four types of rationality, as postulated by Kalberg.